2009
DOI: 10.4049/jimmunol.0801485
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Derived Mast Cells Accumulate in the Central Nervous System During Inflammation but Are Dispensable for Experimental Autoimmune Encephalomyelitis Pathogenesis

Abstract: Reports showing that W/Wv mice are protected from experimental autoimmune encephalomyelitis (EAE, a murine model of multiple sclerosis), have implicated mast cells as an essential component in disease susceptibility, but the role of mast cell trafficking has not been addressed. In this study, we have used both mast cell transplantation and genetic mutations (Cd34−/−, W/Wv, Wsh/Wsh) to investigate the role of mast cell trafficking in EAE in detail. We show, for the first time, that bone marrow-derived mast cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 35 publications
3
42
2
Order By: Relevance
“…The former study highlights that MCs accumulate in the CNS trafficking from the bone marrow during EAE but are dispensable for the development of the disease. 21 Interestingly, although in this study no difference in EAE expression between Kit W-sh/W-sh and Kit þ / þ mice was observed, an increased Ag-specific T-cell proliferation in immunized Kit W-sh/W-sh mice was reported, in line with our findings. The latter study shows that milder clinical signs of EAE in Kit W-sh/W-sh mice correlate with decreased CD8 þ T-cell activation.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The former study highlights that MCs accumulate in the CNS trafficking from the bone marrow during EAE but are dispensable for the development of the disease. 21 Interestingly, although in this study no difference in EAE expression between Kit W-sh/W-sh and Kit þ / þ mice was observed, an increased Ag-specific T-cell proliferation in immunized Kit W-sh/W-sh mice was reported, in line with our findings. The latter study shows that milder clinical signs of EAE in Kit W-sh/W-sh mice correlate with decreased CD8 þ T-cell activation.…”
Section: Discussionsupporting
confidence: 81%
“…It must be noted that some of the results here reported may be associated also to an alteration of histamine signalling in these MC-deficient mice, as histamine has been lately reported to reduce T cell proliferation and IFN-g production in autoreactive T cells. 54 Our data also show some discrepancy with the results obtained by other groups in the Kit W-sh/W-sh strain, showing unchanged 21 or reduced 22 EAE clinical course in these mice in comparison with WT counterpart. The former study highlights that MCs accumulate in the CNS trafficking from the bone marrow during EAE but are dispensable for the development of the disease.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…VEGF, the most important mitogen in the process of angiogenesis, is also secreted by infiltrating eosinophils and MCs (Horiuchi and Weller, 1997). The occurrence of MCs on the vasculature wall, their location at the branch points of vessels, their production of proangiogenic factors (such as VEGF, FGF-2, TGF-β, TNF-α, IL-8, MMPs, tryptases and chymases), suggest indeed a prominent role for MCs in the neo-angiogenetic response after ischemic damage (Bennett et al, 2009;Sayed et al, 2011;Ribatti et al, 2000;2011). MCs further contribute to neo-vascularization after ischemia through the promotion of VEGF production from non-mast cell sources (e.g.…”
Section: Reparative Regenerationmentioning
confidence: 99%